MOTIF PEMERINTAH AUSTRALIA MELALUI PROGRAM HCPI TERHADAP KAUM GAY DAN WARIA DI BALI TAHUN 2009 - Widamahanata, I Gede Fredy; Fasisaka, Idin; Kumala Dewi, Putu Ratih (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2017)
ABSTRACT Since the beginning of the 21st century, the issue of foreign aid is become interesting to be studied in the context of international development. Along the development era of foreign aid is now not only limited through military aspects but also to follow the changes and complex global problems. Since the 1990s, Indonesia is a country with people living with HIV / AIDS which is quite high. This is a concern for the government of Australia until the assistance program called the Indonesia HIV / AIDS Prevention and Care Project (IHPCP) which appeared in 1995 and ended in 2008. The program, hereinafter referred to HIV Coorperation Programme for Indonesia (HCPI), which focus on deployment HIV / AIDS in Bali against gays and transvestites. Gaya Dewata Foundation is their counterparts in realizing some of Australia's aid program in tackling the risk of spreading contagious infection of HIV / AIDS for gay and transgender group in Bali. On the other hand, the condition of the transmission of HIV / AIDS on homosexuals in Australia increased in 2008 and 2012 reached 67%. This study examined using the theory of motive foreign aid with scope of problem that focuses only on the motives of the Australian government in providing assistance to Indonesia to deal with cases of HIV / AIDS, especially on gays and transvestites in Bali. Results and how Australia with Indonesia an agreement in the fight against HIV / AIDS is not the orientation in this study because in this phenomenon is only focused on the motives of the Australian government aid. Key Words: Foreign aid, HIV / AIDS, HIV Coorperation Programme for Indonesia (HCPI), the Australian government, the motives of foreign aid